Arms Risk: The Role of Female Political Representation - DiRienzo, Cassandra (International criminal justice review, 2024)
There are approximately one billion small arms and light weapons (SALW)—rifles, pistols, and light machine guns—circulating throughout the globe, many of which are in the “wrong hands” meaning that they are in the possession of criminals, terrorists, and/or extremists. We hypothesize that greater female political representation has both a direct and an indirect effect on arms risk, or the risk that SALW fall into the “wrong hands.” We contend that greater female political representation directly reduces arms risk as female politicians are more likely to support SALW regulation. Further, greater female political representation indirectly effects arms risk by mitigating conditions necessary for the illicit trade of SALW. Using a causal mediation analysis and a cross-country dataset, we offer empirical evidence that greater female political representation has both a direct and indirect effect in reducing a country's arms risk.